2018
DOI: 10.1007/s11121-018-0887-4
|View full text |Cite
|
Sign up to set email alerts
|

Commentary on Participation in Preventive Interventions

Abstract: In this commentary on the special issue, Preventive Parenting Interventions: Advancing Conceptualizations and Enhancing Reach, operationalization of participation, who engages in prevention interventions, and common themes from the studies are discussed. The papers in the special issue illustrate the importance of studying factors that increase participation in prevention and point out the need for additional research to understand these factors. These papers highlight the diverse conceptualizations of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Also, 69.1% of the sample had dated or been in a romantic relationship in the past year (n = 572). In regard to income level 4 , 58.8% (n = 287) of students reported that their parents/guardians earned over $75,00 per year, 69.4% (n = 394) that their parents/guardians, at least in part, paid for their tuition, and 65.0% (n = 368) that their parents/guardians paid, at least in part, for their room, board, and other living expenses.…”
Section: Sample Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, 69.1% of the sample had dated or been in a romantic relationship in the past year (n = 572). In regard to income level 4 , 58.8% (n = 287) of students reported that their parents/guardians earned over $75,00 per year, 69.4% (n = 394) that their parents/guardians, at least in part, paid for their tuition, and 65.0% (n = 368) that their parents/guardians paid, at least in part, for their room, board, and other living expenses.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…However, recruitment and retention for SA and PA prevention and intervention initiatives remain major challenges in this field 1,2 as in prevention science more widely. 3 Because recruitment is a key issue facing both researchers and practitioners, researchers have begun to examine a broad range of factors associated with participation, 4 including whether or not a potential participant attends an intervention. This initial attendance is also known as intervention uptake.…”
mentioning
confidence: 99%
“…Although most of these studies were conducted during the effectiveness phase, learning what barriers deter participation or what modalities (e.g., online versus home visiting) work best for whom during an effectiveness study has implications for understanding who will adopt an intervention and, in this way, can optimize the population-level impact of EBIs when they scale-up. This is consistent with the TSci Impact framework (Spoth et al 2013) and NIDA's conceptualization of the full spectrum of prevention science(e.g., Sims and Crump 2018) , which highlight that studies at all phases of the prevention intervention research cycle, from program development and design through dissemination, can address research questions that inform the usability and sustainability of EBIs.…”
Section: Concluding Comments and Future Directionsmentioning
confidence: 99%
“…Nonetheless, because findings replicated across multiple model specifications, including across racial and ethnic groups that have previously had lower engagement (O'Brien et al 2012), we believe them to be the best estimate of predictors of parent attendance in VIP through the first 6 months in the current effort. Further, this study examined only attendance, which while important (Reyno and McGrath 2006), is one of several dimensions of participation in interventions (Sims and Crump 2018). Future studies should include additional aspects of participation like parent feedback and interventionist perceptions to create a fuller picture of engagement, as these are likely important predictors of participation (Ingoldsby 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…For early childhood interventions to be maximally effective for population impact and reduce school readiness gaps, however, initial engagement of parents and their continued attendance and participation is critical (Baker et al 2011;Reyno and McGrath 2006). Following recent suggestions for terminology (Sims and Crump 2018), we define initial engagement as the activities related to beginning an intervention, including enrollment and making a commitment to attend an initial session; attendance or retention as taking part in intervention sessions; and participation as taking part in a broader set of program activities. Studies have indicated that each step-from enrollment to attendance to participation-can affect intervention outcomes (Berkel et al 2018).…”
mentioning
confidence: 99%